Night-time in Java. Thoughts on Merapi, Verticality and Paganism - Jean-Baptiste Bing (Revue de Géographie Alpine)
Despite the contemporary Islamic modernisation that manifests itself in Java in the form of new approaches to time and space, the perpetuation of local syncretic practices is reviving vernacular temporalities and spatialities. In Java, the latter appear not only as a framework in which the struggle between two conceptions of Islam plays out but also as resources and challenges for the players involved. This article, the result of two field observation stays, examines an “extreme case”: night-time on the Merapi volcano. The first part highlights the high places and the dense-moments of the volcano’s nightlife, whose mountain and night-time qualities meet and support each other; the second part reframes these practices and representations within the context of conflicts between puritan orthodoxy and local practices, where the night and the mountain play a similar role; finally, the third part conceptualises the space-time link between this place and this moment and hypothesises that, beyond a simple simultaneity, there is a similar relationship to verticality, which is itself regarded as the result of a trajection.